Post-Soviet Protests: The Causes and Consequences of Public Uprisings in Central Asia - Bimal Adhikari; Assem Bazarbek; Madina Shakar (Journal of Eurasian Studies)
What explains individuals’ decision to protest in authoritarian countries? More specifically, what motivates people in Central Asia to take part in public demonstrations? While public expression of dissent is relatively infrequent in Central Asia, they do occur, and a few of them have even resulted in massive political upheavals. Yet scholarly research has largely overlooked the motivations behind these protests and their broader implications. Drawing on a novel dataset on mass mobilization, we identify relative deprivation to be the primary driving force for people’s engagement in protests in Central Asia. Devising policies to ameliorate economic grievances may help the region become more stable, which may in turn result in higher economic growth and development. In the long run, these policies may also result in democratic deepening, as posited by the modernization theory.